Penguatan Tata Kelola Usaha dan Kapasitas Produksi Serta Pemasaran Digital Pupuk Organik Produk Paguyuban Tunggal Rabuk di Desa Kragilan, Mojosongo, Boyolali - Setiawan, Topan; Aryo Putro, Fanny Hendro; Hertini, Etty Sri; Muryanto, Sigit; Chumaeson, Wahyuning; Aziz, Muhammad Abdul (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The Community Partnership Program (PKM) in Kragilan Village, Mojosongo Sub-district, Boyolali, partnered with Paguyuban Tunggal Rabuk to process livestock manure into eco-friendly compost. The program aimed to strengthen the community’s business capacity through the Asset-Based Community Development (ABCD) approach by optimizing local assets and wisdom. PKM activities focused on three key areas: (1) strengthening business governance through mentoring in organizational management, simple financial administration, and effective distribution systems; (2) improving production through technical training, appropriate technology use, and product standardization; and (3) implementing web-based digital marketing to expand market reach, enhance branding, and simplify online transactions. The program outcomes showed improved member skills, greater production efficiency, and expanded consumer networks. Overall, PKM effectively empowered Paguyuban Tunggal Rabuk, fostered local-based business independence, and promoted economic sustainability alongside environmental conservation in Kragilan Village.